2022
DOI: 10.3389/fbioe.2022.824297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attrition Shoes on Kinematics and Kinetics of Lower Limb Joints During Walking

Abstract: Shoe attrition is inevitable as wearing time increases, which may produce diverse influences on kinematics and kinetics of lower limb joints. Excessive attrition may change support alignment and lead to deleterious impacts on the joints. The study identifies the biomechanical influences of aging shoes on lower limb joints. The shoes in the experiment were manually worn in the lateral heel. Nineteen healthy participants, including thirteen males and six females, were recruited to conduct walking experiments wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, Helton et al found that shoes with mild to moderate lateral-torsional stiffness were effective in reducing the lower extremity injury risk among military cadets [36]. Shoe attrition was not analyzed in this study; however, Chen et al recently postulated that shoe attrition has signi cant impacts on the kinematics and kinetics of lower extremity joints [23]. Our study subjects have been tested in already worn shoes that could have in uenced the results; thus, in Latvian Land Forces footwear has been changed regularly if visible shoe attrition persists; before marker placement, no visual damage (eg, asymmetrical shoe heel abrasion) to the combat boots was found.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Helton et al found that shoes with mild to moderate lateral-torsional stiffness were effective in reducing the lower extremity injury risk among military cadets [36]. Shoe attrition was not analyzed in this study; however, Chen et al recently postulated that shoe attrition has signi cant impacts on the kinematics and kinetics of lower extremity joints [23]. Our study subjects have been tested in already worn shoes that could have in uenced the results; thus, in Latvian Land Forces footwear has been changed regularly if visible shoe attrition persists; before marker placement, no visual damage (eg, asymmetrical shoe heel abrasion) to the combat boots was found.…”
Section: Discussionmentioning
confidence: 95%
“…To de ne the shank and foot segments, anatomical markers (n = 12) were attached to the middle shank, the lateral and medial femoral epicondyles, the lateral and medial malleoli, and the head of the 1st, 2nd, and 5th metatarsals, and the posterior calcaneus. The placement of the markers was the same as in previous studies for barefoot and shod conditions [22,23]. For the shod condition, markers were placed after palpation of the anatomical landmark through the shoe.…”
Section: Gait Assessmentmentioning
confidence: 99%
“…Additionally, we did not analyze shoe attrition, but Chen et al recently postulated that running shoe attrition impacts the kinematics and kinetics of lower extremity joints [36], and we do not know if it is the same for the infantry boot. Footwear in the Latvian Land Forces is changed regularly if visible shoe attrition persists, and no visual damage (e.g., asymmetrical shoe heel abrasion) of the infantry boots was found before marker placement during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…The marker set used in this study is similar to the conventional lower-limb gait model marker set (n = 8) and showed good test-retest reliability (ICC > 0.80) [34]. The markers were placed in the same locations as in previous studies for barefoot and shod conditions [35,36].…”
Section: Gait Assessmentmentioning
confidence: 99%
“…The boots were eligible for gait evaluation unless visible signs of attrition were observed.During the gait cycle and the analysis of lower extremity movement, all study participants were fitted with retroreflective spherical markers (n = 12) using double-sided tape. A single examiner marked the subject's anatomical landmarks of the bare foot and shank bilaterally according to the previously used marker set: the middle shank, lateral and medial femoral epicondyles, lateral and medial malleoli, first, second and fifth metatarsal heads, and posterior calcaneus(Chen et al, 2022;Peng et al, 2020). After palpation of the anatomical landmarks through the military boot, markers were attached for shod gait assessment.…”
mentioning
confidence: 99%